KEBIJAKAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA MRANDUNG KECAMATAN KLAMPIS KABUPATEN BANGKALAN - -, Hakip (P3M IAIN KEDIRI, 2018)
Land and building tax is local tax that has been transferred from the central to the regions since the issuance of PDRD Regulation No. 28/2009. Village is one of the institutions authorized as a collecting officer of PBB is required to carry out duties in the execution of the collection of PBB in accordance with Law No. 12 of 1994 on Land and Building Tax in order to support the original revenue areas used for regional development. This research is to explain how the process of implementation of land tax collection and building in Mrandung village of Klampis district of Bangkalan regency. The type of research used is descriptive qualitative with data collection techniques in the form of interviews, document review and analyzed using Van Meter model and Carl Varn Horn. The results of this research indicate that there is no a process of collecting land and building taxes in Mrandung village because the village government of Mrandung replaces the obligation of its citizens in paying off all the indebted taxes owned by the people of Mrandung village. It makes the village government as the management apparatus of PBB at the village level is not Following the procedures in accordance with the laws and regulations of the Building Land Tax Law No. 12 of 1994 on Land and Building Tax and does not obey the regulations in Bangkalan regency namely Bangkalan Regent Regulation No. 60 of 2013 on the Management of Land and Urban Building Tax and Rural. The analysis using Model Van Meter and Carl Van Horn it could be seen that the absence of the process of collection of Land and Building Tax in Mrandung village due to attitude / tendency owned by Mrandung village government which underlies the implementors remain in their own thinking in response to the policy of collection land and building in Mrandung village of Klampis district of Bangkalan regency. Suggestion from this research is that PBB officers in the village should be more active in delivering information to the community, the quality of human resources and understanding of the content of PBB policy should be improved so that in running the PBB in accordance with established procedures.